Pemanfaatan Media Video Pembelajaran Dalam Meningkatkan Prestasi Belajar Siswa PAK Siswa/I SDN158326 Bajamas 2 T.P.2023/2024 - Heppi Situmeang (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Research conducted to improve student achievement at PAK Denman applied the Discovery Learning model by utilizing video media. The subjects in this study were 1st grade students at SDN No 158326 Bajamas 2 Academic Year 2023/2024 as many as 7 people. The results of the study concluded that the application of the Discovery Learning model by utilizing well-designed and planned video media in accordance with the objectives to be achieved it is proven to be able to increase student achievement. After the action of Cycle I obtained results with a completeness percentage of 76.33%, after the action of Cycle II, the average student achievement was 82.04% or an increase of 5.71% compared to cycle I